2012
DOI: 10.1007/s00101-012-2007-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-articular injection of levobupivacaine on articular cartilage and synovium in rats

Abstract: Although more studies are needed before final recommendations can be made, by evaluating the results obtained from this study, the clinical use of intra-articular levobupivacaine can be recommended for arthroscopic knee surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…These findings suggest that intra-articular local anaesthetics, especially when used as infusion, may be related to increased risk of postartroscopic chondrolysis and early osteoarthritis [ 1 ]. Higher concentrations, low pH (< 5), infusion pump usage for longer lasting effect and the use of epinephrine, which decreases pH, are among the factors related to increased chondrotoxicity [ 1 , 10 ]. Dogan et al [ 18 ] also conducted an experimental study on rabbit knees and found that compared to saline in joint cartilage and the synovium, bupivacaine and neostigmine injection histopathologically caused an increase in inflammation, inflammatory cell infiltration, synovial hyperplasia, and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that intra-articular local anaesthetics, especially when used as infusion, may be related to increased risk of postartroscopic chondrolysis and early osteoarthritis [ 1 ]. Higher concentrations, low pH (< 5), infusion pump usage for longer lasting effect and the use of epinephrine, which decreases pH, are among the factors related to increased chondrotoxicity [ 1 , 10 ]. Dogan et al [ 18 ] also conducted an experimental study on rabbit knees and found that compared to saline in joint cartilage and the synovium, bupivacaine and neostigmine injection histopathologically caused an increase in inflammation, inflammatory cell infiltration, synovial hyperplasia, and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Dragoo et al [ 16 ] did not find any signs of increased chondrotoxicity following exposure of in vitro human chondrocytes to 0.25% bupivacaine and 0.5% ropivacaine. Although the analgesic efficacy of intra-articular levobupivacaine has been shown in several human studies, we could find only two histopathological studies evaluating the chondrotoxicity of levobupivacaine in the literature [ 10 , 20 ]. The design of these experimental animal studies, which were also conducted at our university, was very similar to our study and thus has the same limitations of not being directly applicable to human tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the histological sections of the knee joints, the surface of the cartilage, cartilage zones (tangential, intermediate, radial and calcified zone), the synovium and soft connective tissue beyond the synovium were evaluated by two histologists who were blinded to the joint treatment groups. The inflammatory changes were graded in four fields per section and four sections per animal according to a fivepoint scale, based on a similar study of Erden et al [10].…”
Section: Methodsmentioning
confidence: 99%
“…For example, rats can breathe 50% carbon dioxide without problems [41] while humans quickly become unconscious and develop seizures while breathing 10% carbon dioxide [38] indicating significant differences in cardiorespiratory physiology and hence, extrapolation difficulties between rodents and humans. In our experience, rodents are frequently used in basic science research laboratories [9] while swine are more favored in translational research [27].…”
Section: Introductionmentioning
confidence: 99%